Electric-field control of magnetic properties of CoFe2O4 films on Pb(Mg1/3Nb2/3)O3–PbTiO3 substrate - Chen, Lang (2013)
A ferrimagnetic CoFe2O4 film is deposited on piezoelectric Pb(Mg1/3Nb2/3)O3–PbTiO3 (PMN–PT) single crystal substrate by pulsed laser deposition. Using a piezoelectric substrate eliminates the clamping effect prevalent in the conventional composite film systems on passive substrates and facilitates effective strain coupling at the interface. When an electric field is applied to the PMN–PT substrate, the magnetic properties and domain structures of the CoFe2O4 film are altered which demonstrates magnetoelectric coupling between the substrate and the film. The changes observed can be explained using a strain transfer model.